The natural real interest rate and the output gap in the euro area: a joint estimation - Julien Garnier; Bjørn-Roger Wilhelmsen (European Central Bank (ECB), 2005)
The notion of a natural real rate of interest, due to Wicksell (1936), is widely used in current central bank research. The idea is that there exists a level at which the real interest rate would be compatible with output being at its potential and stationary inflation. This paper applies the method recently suggested by Laubach and Williams to jointly estimate the natural real interest rate and the output gap in the euro area over the past 40 years. Our results suggest that the natural rate of interest has declined gradually over the past 40 years. They also indicate that monetary policy in the euro area was on average stimulative during the 1960s and the 1970s, while it contributed to dampen the output gap and inflation in the 1980s and the 1990s.
Keywords: C32; E43; E52; O40; 330; euro area; Kalman filter; output gap; Real interest rate gap; Realzins; Bruttoinlandsprodukt; Eurozone; EU-Staaten; Zustandsraummodell